Original paperEffects of absorbed dose of 131I isotope on the effectiveness of ablation of thyroid remnant tissue - Adamczewski, Zbigniew; Makarewicz, Jacek; Lewiński, Andrzej (Archives of Medical Science, 2007)
Introduction: The aim of the study was the assesment of effective ablative dose of absorbed 131I radiation, based on dosimetric measurements. Material and methods: The study group comprised one hundred (100) patients in whom papillary thyroid carcinoma (PTC, 54 cases) and follicular thyroid carcinoma (FTC, 46 cases) had been diagnosed. The activities of 131I, administered to those patients, ranged from 1643 MBq (44.4 mCi) to 4033 MBq (109 mCi). The following parameters were determined in the patients before radioiodine therapy: the mass of thyroid remnants [M (g)], iodine uptake [U %], and the effective half-life of radioiodine [EHL (days)]. After obtaining the results of measurements, the dose [D (Gy)] absorbed by thyroid remnants was retrospectively calculated by means of our own modification of the Marinelli formula. Additionally the effect of the analyzed parameters on ablation effectiveness was assessed. Results: In 80 patients (80%) the performed ablation was evaluated as effective. The most effective (91%) was the ablation in the group of patients who received an absorbed dose of 2400 Gy or higher. A correlation was found between the absorbed dose and the effectiveness of ablation (rs=0.23; p 1.5 γ (68%) (p<0.03). Conclusions: A correlation has been demonstrated between ablation effectiveness and the 131I dose absorbed by thyroid remnants. The highest effectiveness of ablation was obtained after the administration of D ł2400 Gy.